Exploring the processes and problems in teaching, learning and researching Malay manuscripts - Zulkifli, Zahidah; Abdullah, Noorhidawati (Library & Information Science Unit, Faculty of Computer Science & Technology, University Malaya, 2010)
The paper explores the processes and problems of the Malay manuscripts community which comprises lecturers, students and researchers when teaching, learning and researching on Malay manuscripts. The data was obtained from several interview sessions, focus group discussions and through observations. The case study approach was adopted using lecturers teaching and students enrolled in a philology course and researchers on manuscript studies at the Academy of Malay Studies, University of Malaya. The results indicate that the lecturers mainly uses the “chalk and talk” approach when delivering their course; they refer students to one reference source throughout the course; they indicated that students must be able to read Jawi scripts to follow the course; the main assignment involved transliterating work from old Jawi scripted text into modern romanise Malay; and they would like to have access to more Malay manuscript texts that can be utilised by their students for their assignments. The students confirm that their main assignments involved transliterating work; their main source of reference is their lecturer; they are unaware of the existence of a digital library of Malay manuscripts; and are acceptable to accessing online manuscript resources and being able to hold online discussions with their lecturers and peers about their assignments. The researchers mainly uses printed text for their research; they use the computers mainly to word-process; and felt that online dictionary on classical Malay would help them in their research. The findings on problems and needs express by all three groups are mapped to a proposed framework of online platform for manuscripts studies which includes teaching, learning and researching, utilizing resources provided by MyManuskrip (Digital Library of Malay Manuscripts).